Construção de um protótipo de seguidor solar de um eixo para placas fotovoltaicas - Perez, Felipe José (2018)
This work includes the elaboration of a prototype solar tracker of an axis for photovoltaic panels. Having a reduced scale construction relative to a real application and low cost components, the system proved effective to change the position of a photovoltaic plate over the course of a day in order to keep it perpendicular to solar radiation direct. Equipped with a pair of light sensors based on light-dependent resistors to track the position of the Sun, with a microcontrolled control system and a stepper motor as actuator, the prototype cost about R$ 700,00, with the methodology adopted for its accomplishment being detailed in this study. Five tests were done to prove the operation of the prototype. The first one aimed at the operation of the solar tracker on bench. Using an external power source, since in the internal environment the solar panel does not generate a significant amount of energy, and of a table lamp to simulate the solar radiation, it was possible to prove the correct movement of the photovoltaic plate when moving of the luminaire. Although the system was not able to operate in an autonomous mode, as evidenced in the second test, other experiments were performed under real operating conditions, using an external source of energy, to validate the possibility chosen for sun tracking, according to the objectives of the work. Thus, on a sunny day and another with a completely overcast sky, the prototype was placed on the roof of a building and left running from early morning until late afternoon, moving as planned. Additionally, another test was done on a day that began with a period of Sun between clouds and ended completely cloudy, with the effectiveness of the system once again being proven. In fact, both on days with a predominance of direct solar radiation and on days with predominance of diffuse radiation, the proposed solution demonstrated the validity of the chosen sun tracking technique, which allows the construction of solar trackers with the use of simple luminosity sensors, and the consequent increase of efficiency in the photovoltaic conversion of energy.